2015
DOI: 10.1159/000430815
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary Axis in Non-Functioning Pituitary Adenomas: Focus on the Prevalence of Isolated Central Hypoadrenalism

Abstract: Introduction: Non-functioning pituitary adenomas (NFPA) account for about 40% of pituitary tumors. Pituitary deficiencies are present at diagnosis in 60-80% of NFPA, and, classically, growth hormone (GH) secretion is lost first, while adrenocorticotropic hormone is expected to disappear last. The aim of this study was to evaluate the incidence of multiple or isolated pituitary deficiencies in a large series of NFPA. Materials and Methods: We retrospectively analyzed data on 218 NFPA cases (59% females, 59% wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
9
1
1
Order By: Relevance
“…To our knowledge, this is the first study to describe continued recovery of HPA function after long‐standing SAI in patients with pituitary disorders. Previous studies have shown that 10–32% of patients with sellar masses have an associated SAI at presentation . In particular, the risk of SAI is higher in patients with craniopharyngiomas and hypophysitis such that 24–62% of patients with craniopharyngiomas and up to 50% of patients with hypophysitis have SAI at presentation .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, this is the first study to describe continued recovery of HPA function after long‐standing SAI in patients with pituitary disorders. Previous studies have shown that 10–32% of patients with sellar masses have an associated SAI at presentation . In particular, the risk of SAI is higher in patients with craniopharyngiomas and hypophysitis such that 24–62% of patients with craniopharyngiomas and up to 50% of patients with hypophysitis have SAI at presentation .…”
Section: Discussionmentioning
confidence: 99%
“…Primary diagnoses were NFA (23), prolactinoma (PRLoma) (5), craniopharyngioma (5), GH-producing adenoma (4), hypophysitis (5), Rathke's Cleft cyst (3), empty sella (2), osteolipoma (1), idiopathic (1), oncocytoma (1) and pituitary epithelial neoplasm (1). Of these patients, 11 had conservative management with no surgical intervention, whereas the remaining 40 patients underwent the following procedures: transsphenoidal resection of tumour (35), stereotactic radiation therapy (3), pituitary biopsy (1), craniotomy (1), drainage of pituitary cyst (1), transcortical transventricular endoscopic fenestration with subtotal resection (1) and yttrium treatment (1). The median duration of glucocorticoid therapy prior to discontinuation (if possible) was 37 months (range: 8-112).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations